Translation as communication across languages and cultures - House, Juliane (Routledge, Taylor & Francis Group, 2016)
In this interdisciplinary book, Juliane House breaks new ground by situating translation within Applied Linguistics. In thirteen chapters, she examines translation as a means of communication across different languages and cultures, provides a critical overview of different approaches to translation, of the link between culture and translation, and between views of context and text in translation. Featuring an account of translation from a linguistic-cognitive perspective, House covers problematic issues such as the existence of universals of translation, cases of untranslatability and ways and means of assessing the quality of a translation. Recent methodological and research avenues such as the role of corpora in translation and the effects of globalization processes on translation are presented in a neutral, non-biased manner. The book concludes with a thorough, historical account of the role of translation in foreign language learning and teaching and a discussion of new challenges and problems of the professional practice of translation in our world today. Written by a highly experienced teacher and researcher in the field, Translation as Communication across Languages and Cultures is an essential resource for students and researchers of Translation Studies, Applied Linguistics and Communication Studies.